Efficacy of extracorporeal shockwave therapy in the treatment of postherpetic neuralgia: A pilot study. Issue 12 (March 2020) - Lee, Sung Hyun; Ryu, Kyoung-Ho; Kim, Pyoung On; Lee, Hyo-Won; Cho, Eun-Ah; Ahn, Jin-Hee; Youn, Inyoung; Yang, Kyung Seung
Abstract : Abstract: Established conventional treatments for postherpetic neuralgia (PHN) and postherpetic itch (PHI) are difficult and often disappointing. In this study, the authors investigated the effect and mechanisms of extracorporeal shockwave therapy (ESWT) on pain and itch associated with PHN and PHI. Thirteen patients, 50 to 80 years of age, with symptoms associated with PHN or PHI (duration of persistent pain >3 months) and complaints of pain or itch rated >4 on a numerical rating scale (NRS), were included. ESWT was administered using a shockwave device (Piezo Shockwave 2, Richard Wolf GmbH, Knittlingen, Germany) to skin areas affected by pain or itch. An energy flux density of 0.09 to 0.16 mJ/mm 2 at a frequency of 5 Hz and 2000 impulses was administered at 3-day intervals for 6 sessions. The NRS, 5D-Itch Scale, and Patients Global Impression of Change (PGIC) scale were used to evaluate the efficacy of ESWT. NRS scores of pain and itch and 5D-Itch Scale scores decreased significantly compared with before treatment and at the end of the treatment sessions ( P  < .0001, P  = .001, P  = .0002, respectively). There was a statistically significant difference between PGIC scores, which were checked every 2 sessions ( P  < .0001). ESWT is a noninvasive modality that significantly reduced PHN-associated pain and itch.